P-27 Delivery of the care certificate to local care homes. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Manns, Jane; Bryan, Liz; Morris, Kathy
Abstract : The Care Certificate launched by Health Education England (HEE) this year comprises a set of 15 standards to address the inconsistencies of induction training for new staff entering the health or care profession (Cavendish Review 2013). From April 2015 all new support staff working in health or social care must demonstrate the essential standards within the Care Certificate as part of their overall induction and all existing staff must be appraised against the Care Certificate standards. Learning from participation in the national pilot led to St Christopher's successfully applying to City and Guilds for accreditation for the 'Care Certificate (Cavendish) from St Christopher's'. The 15 standards are taught and assessed holistically with learning contextualised for the setting in which care is being delivered, for example, for local care home staff the needs of patients with dementia, long term conditions, care of the frail elderly and those approaching the end of life are incorporated. With funding from the Local Education and Training Board (LETB), Health Education South London (HESL) this 'hospice' version of the Care Certificate has now been rolled out by the South London Hospice Education Collaborative to 12 local care homes. This is not only about training care home staff to deliver good fundamental care but about empowering care homes to become more effective learning environments. The project has included funding to train a nominated senior member of staff from each care home as a fully qualified assessor achieving the Level 3 QCF Certificate in Assessing Vocational Achievement (CAVA). This will facilitate care homes to be part of the delivery of vocational qualifications for their own staff ensuring future training and educational needs are addressed through a recognised accredited route.